PEDAGOGICAL CONDITIONS OF STUDENTS’ READINESS FOR FUTURE AIR TRAFFIC CONTROLLERS TO PERSONAL HEALTH CARES IN PROFESSIONAL ACTIVITIES - Оргєєва, Світлана Володимирівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the work by pedagogical conditions of students’ readiness for future air traffic controllers to personal health cares professional activities in content correspond motivational, cognitive, active and reflective components to health cares personal preparedness. These detailed and characteristic features of each educational conditions. Established that the consideration and implementation of these educational conditions in the educational process of higher aviation educational institution will ensure efficient operation of the future Aviation specialist towards the formation of students’ readiness for personal health cares